32 Peak Nasal Inspiratory Flow Levels in Children With Allergic Rhinitis and Their Health Related Quality of Life (HRQL) - Nagaraju, Major K. (World Allergy Organization Journal, 2012)
BACKGROUND: Allergic rhinitis impairs the quality of life children. There is paucity of data with regards to clinical profile and health related quality of life (HRQL) of children with Allergic rhinitis in India and hence we studied the clinical profile and measured Peak nasal inspiratory flow (PNIF) of children with allergic rhinitis in an urban population, and assessed their Quality of life. METHODS: Children with moderate to severe persistent Allergic rhinitis, diagnosed as per Allergic Rhinitis and Impact on Asthma (ARIA) guidelines, in the age group of 6 to 18 years were included in this study. The quality of life questionnaire, pediatric and adolescent by Juniper et al was used. PNIF was measured by using ‘In- Check’ peak nasal inspiratory flow meter. RESULTS: Of the 100 children studied, 70 (70%) were in the age group of 6 to 11years and 30/100 (30%) were between 12 and 18 years of age. An equal distribution of sex was observed in 6 to 11 year age group, and in the 12 to 18 year age group there was a male preponderance (1.9:1). Majority (87%) of children in our study had Moderate Allergic rhinitis and 13% had severe Allergic rhinitis. Bronchial asthma, a commonly reported entity in Allergic rhinitis was seen in 19% of the cases. 66% of children in our study had PNIF values of the fifth to 50th percentile where as 24% were in the third to fifth percentile and 10% had their PNIF values less than third percentile. PNIF showed a linear correlation with severity of allergic rhinitis. HRQL assessment showed that children in the 6 to 11 year group had derangement in the activity and physical symptoms domain while children in the12 to 18 year group had predominately involvement of emotional and practical problem domains. Quality of life score worsened with decrease in PNIF. CONCLUSIONS: PNIF is very useful tool to quantify the nasal obstruction in Allergic Rhinitis. PNIF is easy to administer, reproducible and correlates well with the severity of the disease. HRQL assessment helps us to do psycho educational training to adhere compliance.